PENGARUH IKLIM ORGANISASI, SEMANGAT KERJA, DAN KEMAMPUAN KERJA TERHADAP KINERJA PEGAWAI KANTOR PELAYANAN PAJAK PRATAMA KEDIRI - Ulun Na'im (REVITALISASI : Jurnal Ilmu Manajemen, 2019)
This study aims to: (1) know and analyze the effect of organizational climate on performance of employees at Tax Office Kediri; (2) to know and analyze the influence of work morale on the performance of employees of Tax Office Primary Kediri; (3) to know and analyze the influence of work ability on the performance of the employees at Tax Office Kediri; (4) to know and analyze the influence of organizational climate, work spirit and work ability simultaneously on the performance of employees at Tax Office Kediri. This research was conducted at at Tax Office Kediri in Brawijaya Street 6th , Kediri. Implementation of the research started from March 2017 to May 2017. Respondents in the study were all employees who amounted to 85 people. The results showed that: (1) Together organizational climate factors, morale and work ability have a positive and significant effect on the performance of employees at Tax Office Kediri; (2) From the regression analysis on the influence of individual variables, it can be seen that organizational climate, work morale and work ability have a positive and significant effect on the performance of employees at Tax Office Kediri, as evidenced by the value of regression coefficient and t- Each larger than t-table; (3) Job competency factors have a dominant contribution in influencing employee performance.